Culture of yeast in a perfluorocarbon/water system - Elibol, M (Chapman Hall Ltd, 1997)
Perfluorodecalin at 5% (v/v) did not affect the growth of Saccharomyces cerevisiae in a 2-L bioreactor. The biomass concentration, however, was increased by using 10% and 15% (v/v) perfluorodecalin from 16.4 g/l (control) to 24.8 g/l and 26.2 g/l, respectively. The maximum values of K(L)a and O-2 uptake rate was almost 1.5 times higher than those obtained in the control run.
Keywords: Immobilized Cells; Oxygen-Transfer; Perfluorochemicals; Enhancement; Carrier; Model